Pengaruh Kemampuan Psikis Dan Psikologis Serta Lingkungan Sosial Dan Non Sosial Terhadap Peningkatan Penjualan Pada Karyawan Metro ACC Di Kota Metro - Kuncoro Budi Riyanto; Nina Lelawati; Fadhil Ilham (Jurnal Manajemen DIVERSIFIKASI, 2024)
Sales in the marketing process within a company is an important factor for a company, because failure to sell goods will result in the development of the company in the future. For this reason, companies must try to find the right strategy in order to survive and be able to meet the goals to be achieved by the company in the form of maximum profit by increasing sales. This study aims to determine the influence of psychic abilities, psychological, social and non-social environment together on increasing sales of employees at Metro ACC Metro City. The research design is quantitative research or verification research. The method used in this research is the ability of psychic, psychological, social and non-social environment as well as increasing sales. The population and research sample were all employees at Metro ACC Metro City with a total sample taken of 30 people. Data collection techniques using a questionnaire. The analytical tool used is data quality analysis and Multiple Linear Regression with the SPSS program. The results showed that psychic abilities, psychological abilities and the social environment had a significant effect on increasing sales, while the non-social environment had no significant effect on increasing sales. Simultaneous test results show the ability of psychic, psychological, social environment and non-social environment together have a significant effect on increasing sales.